Effect of telephone-monitored home-based cardiac rehabilitation exercise on functional capacity and quality of life in heart failure patients in a lower-middle-income country. (11th May 2022) - Huq, FN; Momenuzzaman, NAM; Chowdhury, AW; Hoque, MM; Khan, KN; Begum, F; Shafique, AM; Anis, R; Rahman, MA; Nahar, S; Chakraborty, S; Ahmad, T; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Chronic heart failure (CHF) prevails as one of the major cardiovascular diseases in lower-middle-income countries (LMICs) like Bangladesh. Home-Based Cardiac Rehabilitation (HBCR) is a cost-effective method of secondary prevention of chronic heart failure which, if provided, might not only improve the health status of the patients but might also reduce the financial and hospitalization burden on the health care system of these countries. The study aims to assess the scope and benefits of HBCR in such low resource settings. Purpose: The study evaluates the effect of telephone-monitored HBCR exercise programme in improving the functional capacity and quality of life (QoL) in patients of CHF with reduced ejection fraction due to ischemic heart disease (IHD). Method: This self-controlled interventional study was conducted from August 2019 to July 2020 at a heart failure clinic, a tertiary healthcare centre in Bangladesh. A total of 115 patients of CHF with ejection fraction <40% and in NYHA class II and III were included in the study according to selection criteria. The functional capacity of the patients was evaluated by NYHA classification and 6-minute walk test. The quality of life of the patients was evaluated by Minnesota Living with Heart Failure Questionnaire (MLHFQ). All patients were advised to perform HBCR exercise as per recommended guideline and were telephone-monitored 2-weekly. After the 3-months study period, the participants were divided into compliant and partial compliant groups based on their adherence to the guideline. Repeat evaluation of patients' condition was carried out. Results were then compared within the groups and data was analyzed through appropriate statistical methods. Results: Significant improvement of NYHA class (p<0.05), and 6-minute walk test distance (6MWTD) (1102.01±215.90 feet vs 1243.30±217.86 feet; p<0.001) were noticed after the rehabilitation programme. Improvement of total MLHFQ score was also observed (35.53±14 vs 28.22±12.84; p<0.001) at 3-months follow up. The functional capacity and quality of life of the patients in both the compliant and partially compliant groups showed significant improvement after the rehabilitation programme (p<0.001); though no difference was found in the indicators when compared between compliant vs partially compliant groups after rehabilitation except for 6MWTD (1302.86±219.61 feet vs 1230.71±212.284 feet, p<0.001). Conclusion: From the results, it can be concluded that any amount of routine exercise tends to improve quality of life and symptoms in patients of chronic heart failure with reduced ejection fraction. However, to achieve the best effect in functional capacity and overall health status, the addition of a structured exercise programme like HBCR can be beneficial for proper rehabilitation in low resource settings. Further validation of the results is recommended through randomized control trials in larger study groups.